Australia : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2017)
This Selected Issues paper examines the adjustment of Australian labor markets to the recent adverse shocks. Australia's labor markets were not severely impacted by the global financial crisis and are adjusting smoothly to the sizeable commodity prices bust and mining investment downturn. However, some labor market indicators suggest persistent weaknesses. There does not appear to be a significant increase in structural employment in the wake of the commodity prices bust and mining investment decline. Increased flexibility in average hours per worker has likely moderated employment reduction in downturns and prevented a larger increase in unemployment in the wake of the mining investment downturn. At the same time, elevated underemployment signals additional slack, and is likely weighing down wage growth.